The Window Shopping Method to improve English Speaking Skills in Pocedure Text at SMPIT Yapidh Jati Asih - Chotimah, Chusnul; Astiyandha, Tauricha; Fadhil, M. Rizky (Akademika : Jurnal Teknologi Pendidikan, 2024)
The aim of this research is to to improve students’ English speaking skill using window shopping method in procedure text material at SMPIT Yapidh Jati Asih. The research method is quantitative experiment method. This research is conducted about six months. The populations in this research are 157 students on grade IX of SMPIT Yapidh Jati Asih and 55 students as sample in experiment class and control class. There are 30 students in experiment class and 20 students in control class. The technique of sampling is random sampling. The instruments that used in this research are pre-test, post-test and questionnaires. Based on the results of hypothesis testing using the t test, the sig value was 0.00 according to the test criteria, so H0 was rejected and Ha was accepted. Then, the response percentage with Yes = 99% and No = 1%. These results show that students are very interested using window shopping method to improve English speaking skills in procedure text material.